Potencial de produção de biogás com mistura de dejetos suínos e lodos de ete de frigoríficos e laticínios em biodigestor anaeróbio - Feldkircher, Tiago (2015)
The growing need for wastewater treatment and control of disposal of sludge, residues and waste of agricultural production (mainly of pigs) worries the society because of the major environmental impacts that the improper disposal may result. Because of this and targeting the possibility of power generation through an anaerobic digestion system, with the reuse of this waste, this study aims to quantify and qualify the generation of biogas from the anaerobic digestion in different substrates derived from an Company active in different segments (primary production, chicken and poultry slaughterhouses and dairy industry) of the countryside of Rio Grande do Sul. There were performed six experiments in the Bioreactor Laboratory of Univates University Center, by using reactors of one liter, which were filled with 600 mL of different substrates at various concentrations of each substrate and in bench scale, and after filled, the reactors were kept in greenhouse under temperature control at 35°C. Performed through batch processes, the biogas generated in each experiment was quantified by using a device developed by the laboratory itself. The methane present in this biogas was quantified by a specific sensor called Advanced Gasmetter, of the company PRONOVA AnalysetechnichGmbH&Co. Different results were obtained for each mixture of substrates; the largest amount of biogas was 13.282,72 mL, observed in sample 1 of the VI experiment, which also showed the greatest concentration of methane, that was 8.897,72 mL. It was possible to verify that the cellulosic casing and the float sludge are great increment for increasing the production of biogas and consequently methane in the digestion process. The quantification of substrates also presented an satisfactory volume for possible construction of a digester in full scale aiming the energy generation.